Pharmacological profile and toxicity of fluorescein-labelled sinistrin, a novel marker for GFR measurements - Pill, Johannes; Issaeva, Oxana; Woderer, Stefanie; Sadick, Maliha; Kränzlin, Bettina; Fiedler, Fritz; Klötzer, Hans-Martin; Krämer, Uwe; Gretz, Norbert (Naunyn-Schmiedeberg's archives of pharmacology, 2006)
There is an evident and growing medical need for an accurate determination of kidney function for a broad spectrum of indications. The glomerular filtration rate (GFR) is the most accepted indicator of renal function. Due to difficulties in performing the test, GFR is currently determined rarely in clinical practice. A procedure for such GFR determination has to be safe, accurate and easy to handle. By using the new compound fluorescein isothiocyanate-sinistrin (FS) these requirements are met. The pharmacological profile and tolerability of FS, selected from among various newly synthesized, labelled compounds intended for use as GFR markers, was characterized in male Sprague-Dawley rats following i.v. application. Using the newly described fluorometric method, FS can be determined much more easily in serum and urine than with the established enzymatic method. After i.v. dosing, FS concentrations in serum declined rapidly in various experimental groups to a comparable extent (t1/2, mean±SD: 22.4±8.3 to 26.2±5.4 min). Its increase after unilateral nephrectomy reflects the loss of filtration capacity. Comparable concentration-time curves of FS in serum measured fluorometrically and enzymatically suggest no relevant alteration of pharmacokinetic behaviour by the labelling. This notion is supported by the high urinary excretion rate and absence of biliary excretion. The higher sensitivity of the fluorometric method suggests a dose of FS of 100 mg in humans compared with 5 g of sinistrin or inulin. FS was well tolerated after single and multiple applications. On the basis of these results, the kinetics of FS are comparable with the gold standard inulin or sinistrin, but FS is superior in handling. Providing the data can be transferred from rat to human, determination of GFR using the new method should result in an improvement of acceptance by both physicians and patients.
Gesehen am 22.06.2022